Vision-mediated feeding behaviour of early juvenile Sultan fish, Leptobarbus hoevenii - Lim, Leong Seng; Thumronk Amornsakun; Au, Hsein-Loong; Audrey Daning Tuzan; Hon Jung Liew; Yukinori Mukai; Saleem Mustafa; Gunzo Kawamura (Wiley-Blackwell Publishing, 2021)
The Sultan fish, or ‘Jelawat’, Leptobarbus hoevenii is a cyprinid with a natural distribution in streams, rivers and lakes of some Southeast Asian countries, including Malaysia and Thailand (Mohsin & Ambak, 1983; Vidthayanon et al., 1997). It has value as a freshwater food fish (Mohsin & Ambak, 1983; Roberts, 1989), and its flesh is rich in protein, vitamin B and minerals (Tee et al., 1989). The Sultan fish has been introduced into several countries, including Taiwan and China, for aquaculture and as an ornamental species (Liao et al., 2001; Xiong et al., 2015). Captive breeding, seed production and farming techniques of this fish have been established (Liao et al., 2001; Meenakarn, 1986; Saidin et al., 1988; Truong et al., 2003), and there is information available about its feeding and nutritional requirements (Au et al., 2020). However, the major sensory modalities used by L. hoevenii at early life-history stages to detect prey are still unknown.